Molecular Analysis In The Management Of Congenital Adrenal Hyperplasia (CAH) And Ambiguous Genitalia. - Isa, M.N.; Muhamad, Y.K.; Fuziah, M.Z.; Rus Anida, A.; Sidek, M.Ros; Ramli, S.F.; Adam, N. (2002)

(untitled)
Patients presenting with ambiguous genitalia (AG) often pose a dilemma to the attending clinicians with regard to sex assignment.